Recombinant SARS-CoV-2 RBD with a built in T helper epitope induces strong neutralization antibody response. Issue 8 (22nd February 2021) - Su, Qiu-Dong; Zou, Ye-Ning; Yi, Yao; Shen, Li-Ping; Ye, Xiang-Zhong; Zhang, Yang; Wang, Hui; Ke, Hong; Song, Jing-Dong; Hu, Ke-Ping; Cheng, Bo-Lin; Qiu, Feng; et al.
Highlights: RBD linked TT peptide was prepared to high homogeneity at a considerable capacity. The molecule could stimulate strong humoral and cellular immune response in mice. It would be the most economical to prevent and eliminate COVID-19 on a global scale. Abstract: Without approved vaccines and specific treatments, COVID-19 is spreading around the world with above 26 million cases and approximately 864 thousand deaths until now. An efficacious and affordable vaccine is urgently needed. The Val308 – Gly548 of spike protein of SARS-CoV-2 linked with Gln830 – Glu843 of Tetanus toxoid (TT peptide) (designated as S1-4) and without TT peptide (designated as S1-5) were expressed and renatured. The antigenicity and immunogenicity of S1-4 were evaluated by Western Blotting (WB) in vitro and immune responses in mice, respectively. The protective efficiency was measured preliminarily by microneutralization assay (MN50). The soluble S1-4 and S1-5 protein was prepared to high homogeneity and purity. Adjuvanted with Alum, S1-4 protein stimulated a strong antibody response in immunized mice and caused a major Th2-type cellular immunity supplemented with Th1-type immunity. Furthermore, the immunized sera could protect the Vero E6 cells from SARS-CoV-2 infection with neutralizing antibody titer 256. Recombinant SARS-CoV-2 RBD with a built in T helper epitope could stimulate both strong humoral immunity supplemented with cellular immunity in mice, demonstrating that it could be a promising subunit vaccine candidate.